INTERSECTING MEDICAL AND LEGAL RESPONSIBILITIES IN INDONESIA - Komalasari, Rita; Mustafa, Cecep (Faculty of Law, Universitas Lampung, 2024)
The primary objective of this research is to illuminate the evolution of medical responsibility in Indonesia over time. By examining the complex interplay between law and medicine, social transformations, medical advancements, and shifting legal perspectives, this study seeks to enhance understanding of medical responsibility in Indonesia. Utilizing an interdisciplinary approach grounded in the